Porous Carrageenan-Derived Carbons for Removal of Pb(II) Ions from Aqueous Solution - Annissuzzaman, S M; Mansa, Rachel Fran; Elkes, Richmond Pillai (ASEAN Journal of Chemical Engineering, 2023)
Activated carbon (AC) is a widely used adsorbent that can be applied to remove lead (Pb(II)) ions from wastewater. In the current work, carrageenan was used as a precursor to prepare carraggenan based activated carbon (CAC) using potassium hydroxide (KOH) as a chemical activating agent for Pb(II) ions adsorption from aqueous solution of lead nitrate (Pb(NO3)2). The preparation process involved activation of the carrageenan with KOH at a ratio of 1:4 followed by carbonization at 700oC for 4 h. Physical and chemical characterization of synthesized CAC was conducted to understand surface morphology and functional groups. As the scanning electron microscope (SEM) analysis found, the CAC particle sizes are, on average 25.11 µm before adsorption and 39.21 µm after adsorption. Functional group studies proved that the adsorbate had been adsorbed into the CAC by showing a band stretch of the nitrile group in the Fourier transform infrared (FTIR) spectroscopy analysis. The adsorption process was optimized by changing the temperature of adsorption, dosage of adsorbent, and initial concentration of adsorbate. At the optimum conditions, maximum Pb(II) ions adsorption on the CAC was achieved by 99.04%. Throughout this study, the highest capacity of CAC was determined to be 1.95 mg/g, while the minimum capacity was found to be 0.19 mg/g. Langmuir and Freundlich isotherm were studied to understand adsorption mechanisms. The results suggested that the Langmuir isotherm model fits better than the Freundlich model with a regression coefficient of 0.9845. Pseudo-first-order and pseudo-second-order kinetic models were applied to test the experimental data. Pseudo-second-order exhibited the best fit data for kinetic studies with a regression coefficient of 0.9996, indicating that the adsorption of lead using CAC is limited by the chemisorption process.